A further study of transportation problems on South African university campuses - Wall, Kevin Charles (Department of Civil Engineering, 2016)
This thesis surveys the transportation problems of universities in RSA, and solutions proposed thereto. The transportation problems referred to are problems of access to and egress from the campus; internal circulation on the campus (whether of vehicles or pedestrians); and parking on the campus. Universities were asked to rank in priority order a series of problem statements. Using their replies as a base, a questionnaire was drawn up, and was posted to all eleven White universities, plus the Universities of Durban-Westville and the Western Cape. Information requested included population figures in various staff/student and resident/commuter categories, parking demand and provision, modal split, public transport supply and use, and measures to cope with future increase in traffic. Despite a very satisfactory response, there remain gaps in the data, especially on the question of modal split. Visits were paid to most of the universities planning and administrative staff were interviewed. A comparison with a similar study, done in 1970/1971, yields information on trends. Particularly, it is encouraging to note the improvement in the scope and standard of transportation planning on some of the campuses. Overseas information which could make a contribution to a better understanding of the RSA situation was gathered by means of a questionnaire survey and a literature survey. The countries selected for this purpose, by reason of the similarity of key socio-economic characteristics of their population to RSA data were Australia, New Zealand and Canada. Additional information was gathered, by means of a limited literature survey and a few visits, from universities in UK and USA. This information was critically assessed on its applicability to RSA needs. From this mass of information, factors that influence campus transportation problems are seen to emerge. In the light of this understanding, generalised solutions that are proposed from time to time for the transportation problems at particular universities are commented on in the thesis.